2016
DOI: 10.1016/j.bbi.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gp120 in mice evokes anxiety behavior: Co-occurrence with increased dendritic spines and brain-derived neurotrophic factor in the amygdala

Abstract: Human immunodeficiency virus type 1 (HIV) infection of the brain produces cognitive and motor disorders. In addition, HIV positive individuals exhibit behavioral alterations, such as apathy, and a decrease in spontaneity or emotional responses, typically seen in anxiety disorders. Anxiety can lead to psychological stress, which has been shown to influence HIV disease progression. These considerations underscore the importance of determining if anxiety in HIV is purely psychosocial, or if by contrast, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
4
15
0
Order By: Relevance
“…Therefore, we determined whether HSV-HF mice exhibited increased anxiety-like behaviors in a light-dark preference test and a marble bury assay. Other researchers have reported decreased exploration and increased marble-burying in mouse models of immune system activation and obesity (Andre et al, 2014; Bachis et al, 2016; Malkova et al, 2012; Paris et al, 2014; Pascual et al, 2015). At 3 m p.i., mice were tested by two robust behavior tests for anxiety: light-dark preference and marble burying.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, we determined whether HSV-HF mice exhibited increased anxiety-like behaviors in a light-dark preference test and a marble bury assay. Other researchers have reported decreased exploration and increased marble-burying in mouse models of immune system activation and obesity (Andre et al, 2014; Bachis et al, 2016; Malkova et al, 2012; Paris et al, 2014; Pascual et al, 2015). At 3 m p.i., mice were tested by two robust behavior tests for anxiety: light-dark preference and marble burying.…”
Section: Resultsmentioning
confidence: 94%
“…Specifically, sensory input is transformed to motor output via representational knowledge and executive functions (Keeler and Robbins 2011). At the most basic level, HIV-1 seropositive individuals (Minassian et al 2013) display prominent alterations in preattentive processes (sensorimotor gating); deficits which have been translationally modeled across multiple biological systems used to model HAND (e.g., HIV-1 Tg rat: Moran et al 2013, McLaurin et al 2017; stereotaxic injections of HIV-1 viral proteins: Fitting et al 2006aFitting et al , 2006b; gp120 transgenic mice: Henry et al 2014, Bachis et al 2016; Tat transgenic mice: Paris et al 2015). Alterations in the core components of cognitive function, including key components of both representational knowledge (e.g., attention, long-term episodic memory) and executive function (e.g., flexibility, inhibition), have also been reported in clinical (e.g., Heaton et al 2011;Maki et al 2015;Kanmogne et al 2018) and preclinical (e.g., Lashomb et al 2009;Moran et al 2014;Repunte-Canonigo et al 2014;McLaurin et al 2018McLaurin et al , 2019a studies.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological features observed in GFAP-gp120tg mice include: 1) Loss of neuronal dendrites at 3, 4–5, 6, 10, 12 and 20 months of age (Garden et al , 2002; Kang et al , 2010; Maung et al , 2014; Thaney et al , 2017; Toggas et al , 1994) (Maung and Kaul, unpublished) , (see Figure 1 for immunofluorescence staining of cerebral cortex of 6 months-old mice); 2) loss of synapses at 3, 4–5 and 6 months (Maung et al , 2014; Thaney et al , 2017; Toggas et al , 1994); 3) activated microglia at 3, 4–5, 6, 10 months (Kang et al , 2010; Maung et al , 2014; Thaney et al , 2017; Toggas et al , 1994); 4) Astrocytosis at 3, 4–5, 6 and 10 months (Kang et al , 2010; Maung et al , 2014; Thaney et al , 2017; Toggas et al , 1994); 5) Compromised neurogenesis at 2, 4 to 5 and 8 months (Avraham et al , 2015; Avraham et al , 2014b; Crews et al , 2011; Fields et al , 2014; Lee et al , 2013; Lee et al , 2011; Okamoto et al , 2007; Steiner et al , 2015); 6) Behavioral impairment: GFAP-gp120tg mice display, in comparison to non-tg littermate controls, behavioral changes or impairment. At 6 months gp120tg mice show increased anxiety-like behavior in open field, light/dark transition task, and prepulse inhibition tests (Bachis et al , 2016). At 9 to 12 months, GFAP-gp120tg mice display reduced swimming velocity, and compromised spatial learning and retention (D’hooge et al , 1999; Hoefer et al , 2015; Maung et al , 2014) as well as reduced contextual but not cued fear conditioning (Kaul et al, unpublished) .…”
Section: The Phenotype Of Gfap-hivgp120tg Micementioning
confidence: 99%
“…This investigation found (30–35 %) reductions in the kinetics of systems XAG and xc- in both neurons and glia of the striatum, but not hippocampus, of HIVgp120tg mice compared to non-tg wild-type controls (Melendez et al , 2016). Also, an increased number of spines in the amygdala and higher levels of brain-derived neurotrophic factor and tissue plasminogen activator were associated with an elevated level of anxiety-like behavior in 6 months-old GFAP-gp120tg mice in comparison to age-matched wild-type controls (Bachis et al , 2016). A proteomics study of synaptosomes found that the ratio of activated, phosphorylated to total Akt was diminished in forebrain of GFAP-gp120tg mice compared to non-tg wild-type controls, indicating compromised signaling of the pro-survival protein kinase pathway (Banerjee et al , 2012).…”
Section: Research Topics and Studies Using Gfap-hivgp120tg Micementioning
confidence: 99%
See 1 more Smart Citation